2011
DOI: 10.1371/journal.pgen.1002154
|View full text |Cite
|
Sign up to set email alerts
|

Integrating 5-Hydroxymethylcytosine into the Epigenomic Landscape of Human Embryonic Stem Cells

Abstract: Covalent modification of DNA distinguishes cellular identities and is crucial for regulating the pluripotency and differentiation of embryonic stem (ES) cells. The recent demonstration that 5-methylcytosine (5-mC) may be further modified to 5-hydroxymethylcytosine (5-hmC) in ES cells has revealed a novel regulatory paradigm to modulate the epigenetic landscape of pluripotency. To understand the role of 5-hmC in the epigenomic landscape of pluripotent cells, here we profile the genome-wide 5-hmC distribution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
227
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 264 publications
(257 citation statements)
references
References 27 publications
23
227
1
6
Order By: Relevance
“…Whereas telomere-specific aberrant repair might elevate substitutions directly (29), the mutagenicity of recombination has been debated (2, 31). GC richnessmeasured at 45% vs. 39.8% genome median-agrees well with abundance of genes and functional elements in the hot state, as do abundance of open chromatin (32), enrichment for 5-hydroxy methylcytosines (33), and early replication timing (34) (Fig. 2B and Table 2; see also below).…”
Section: Resultssupporting
confidence: 67%
“…Whereas telomere-specific aberrant repair might elevate substitutions directly (29), the mutagenicity of recombination has been debated (2, 31). GC richnessmeasured at 45% vs. 39.8% genome median-agrees well with abundance of genes and functional elements in the hot state, as do abundance of open chromatin (32), enrichment for 5-hydroxy methylcytosines (33), and early replication timing (34) (Fig. 2B and Table 2; see also below).…”
Section: Resultssupporting
confidence: 67%
“…Immunostaining of 5hmC was done per the methods in the literature with suitable modification. 78 Generally, cells after different treatments were fixed with 4% paraformaldehyde for 15 min at 4 °C and washed 3 times with 1× PBS buffer (Gibco, 10010). Cell membrane was permeabilized by 0.4% Triton X-100 (Sigma, T8787) for 30 min and washed with PBS for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, two recent studies showed that two methyl CpG binding proteins, MeCP2 and Mbd3, preferentially bind to 5hmC and may have important roles in transcription regulation 20,21 . Previous studies indicate that 5hmC is enriched in the exons of highly expressed genes in brain tissues, and in cis-regulatory elements such as active enhancers, insulatorbinding sites in ESCs [22][23][24][25][26][27][28] . Enrichment of 5hmC is also found in the promoter region of polycomb-repressed 'poised' genes in ESCs [23][24][25]27 , which disappeared in the adult brain 29 .…”
mentioning
confidence: 99%
“…Previous studies indicate that 5hmC is enriched in the exons of highly expressed genes in brain tissues, and in cis-regulatory elements such as active enhancers, insulatorbinding sites in ESCs [22][23][24][25][26][27][28] . Enrichment of 5hmC is also found in the promoter region of polycomb-repressed 'poised' genes in ESCs [23][24][25]27 , which disappeared in the adult brain 29 . By comparing the genomic distribution of 5hmC in mouse hippocampus and cerebellum at three different ages, we have shown that it exhibits dynamic changes during brain development and aging 29 .…”
mentioning
confidence: 99%